Fas/FasL Signaling Regulates CD8 Expression During Exposure to Self-Antigens - Flores-Mendoza, Giovanna; Rodríguez-Rodríguez, Noé; Rubio, Rosa M.; Madera-Salcedo, Iris K.; Rosetti, Florencia; Crispín, José C. (Frontiers in Immunology, 2021)
Activation of self-reactive CD8+ T cells induces a peripheral tolerance mechanism that involves loss of CD8 expression. Because genetic deficiency of Fas and Fasl causes the accumulation of double-negative (DN; CD3+ TCR-alpha/beta+ CD4- CD8-) T cells that have been proposed to derive from CD8+ cells, we decided to explore the role of Fas and FasL in self-antigen induced CD8 downregulation. To this end, we quantified Fas and FasL induction by different stimuli and analyzed the effects of Fas/FasL deficiency during a protective immune response and after exposure to self-antigens. Our data describes how Fas and FasL upregulation differs depending on the setting of CD8 T cell activation and demonstrates that Fas/FasL signaling maintains CD8 expression during repetitive antigen stimulation and following self-antigen encounter. Together, our results reveal an unexpected role of Fas/FasL signaling and offer a new insight into the role of these molecules in the regulation of immune tolerance.